Success factor analysis for cloud services: a comparative study on software as a service. (24th April 2020) - Nedbal, Dietmar; Stieninger, Mark
The emergence of cloud computing has been triggering fundamental changes in the information technology landscape for years. The proliferation of cloud services gave rise to novel types of business models, the complexity of which results from numerous different factors critical to a successful adoption. However, when it comes to improvement activities by cloud service providers, due to their multifacetedness, the challenge lies in figuring out where to start. Furthermore, the acuteness of actions to be taken varies among different settings. Thus, we propose the success factor analysis as an approach to prioritise improvement activities according to their acuteness, which is thereby indicated by the gap between the priority and the actual performance of a particular factor. Results show that the factors with the overall highest gap are security & safety, trust, and costs. Overall, the strengths of cloud services are seen in technical features leading to a good ease of use, a positively perceived usefulness, and a broad availability.